Handbook of Climate Services - Walter Leal Filho (Springer International Publishing., 2020)
This book explores climate services, including projections, descriptive information, analyses, assessments, and an overview of current trends. Due to the pressures now being put on the world’s climate, it is vital to gather and share reliable climate observation and projection data, which may be tailored for use by different groups. In other words, it is essential to offer climate services. But despite the growth in the use of these services, there are very few specialist publications on this topic. This book addresses that need. Apart from presenting studies and the results of research projects, the book also offers an overview of the wide range of means available for providing and using climate services. In addition, it features case studies that provide illustrative and inspiring examples of how climate services can be optimally deployed.